Narratives of women about motherhood in a context of socio-health intervention in early childhood in Chile today - Donoso, Claudia Calquín; Arrau, Rodrigo Guerra; Vásquez, Sebastián (Saúde e Sociedade, 2020)
The results of a study aimed at knowing the narratives about motherhood and the network of meanings attributed to the benefits of a state system of child health care, in a group of users in the city of Santiago, Chile, are presented. Through a qualitative-narrative strategy, three narratives about motherhood are presented in the context of intervention: conversion, entrepreneurial and ambivalent. It is concluded that the care device is a central reference in the experience of motherhood as it offers meanings about ideal motherhood and guided by experts. We appreciate that the objects for the upbringing that the system provides, play an important role for the construction of the meanings around the maternity itself and the state benefits. The multiplicity of positions that these narratives offer show the ways in which women self-produce as mothers but also the identifications, resistance, confrontations and questions in key areas for the system itself, such as the promotion of breastfeeding.